Improving surgical training (2020)
Improving Surgical Training is a programme piloting an innovative, evidence-based approach to training. It was developed in response to the Shape of Training report which reviewed postgraduate training and recommended changes in medical education to meet the demands of the modern NHS. A series of initiatives have been developed to enhance the experience for surgical trainees not only to encourage a more focussed and supported method, but also to improve their job satisfaction. The initiatives have combined a greater emphasis on time for training provided by trainers with allocated time for training with multidisciplinary teamworking and the use of technology enhanced learning with simulation of both technical and nontechnical skills. The pilot started in 2018 with core training in general surgery and has been expanded to include vascular surgery, urology and trauma and orthopaedics over the last 2 years. Initial feedback from both trainees, trainers and schools of surgery have identified different challenges to aid implementation. The programme is being very carefully evaluated by an independent company as well as careful oversight by the General Medical Council which are paramount to its success.